THE OUTCOME OF BASIC LIFE SUPPORT TRAINING AMONG SENIOR HIGH SCHOOL STUDENTS IN MALANG, EAST JAVA, INDONESIA: A PRELIMINARY STUDY - Tjahjono, Cholid Tri; Arthamin, Maimun Zulhaidah; Satwikajati, Sawitri; Afifah, Yuri; Lestari, Defyna Dwi; Wulandari, Ayu Pramitha (Journal of Community Health and Preventive Medicine, 2024)
The purpose of this research is to report the influence of BLS training on the knowledge and life support skills of senior high school students.. We did an experimental study in one of the senior high schools in Malang City. First-year until third-year students conducted a BLS training. The use of automated external defibrillators and chest compressions were addressed in a 3.5-hour simulation-based session. We used pre-and post-tests to evaluate the outcome of BLS training with multiple-choice questions. Student t-tests were used to compare scores. According to our analysis, the average score before and after the test went from 80 to 94.19 (p<0.001). Following the instruction, over 90% of the students were able to carry out every step of automated external defibrillation and BLS. To sum up, high school students can learn BLS through a simulation-based method; the training validates their attitude and equips them with essential knowledge and skill sets, enhancing their confidence in BLS performance.